MODERN APPROACHES TO MANAGING THE COMPETITIVENESS OF A CONSTRUCTION ENTERPRISE ACCORDING TO ESG CRITERIA - LIVOSHKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The difficult conditions of doing business in Ukraine during wartime should not affect the change in approaches to managing the competitiveness of economic entities. Enterprise competitiveness management is a certain aspect of enterprise management aimed at the formation, development and realization of competitive advantages and ensuring the viability of the enterprise as a subject of economic competition. The great destruction caused by the military invasion of the territory of Ukraine changed the market and the basic principles of its functioning. The competitiveness of the enterprise is the ability to withstand competition compared to similar objects in this market. It shows the level of development of this enterprise compared to the level of development of competing companies in terms of the degree of satisfaction with their work, goods, and services for the needs of society. Most of the construction companies were forced to leave the market, and those that remained need to review the criteria of their work. The social environment has a significant impact on the competitiveness of a construction enterprise. The modern interpretation of the concept of competitiveness as a multifactorial process of implementation of competitive relations assumes the most important condition for its implementation - modern management of the competitiveness of the enterprise. Social responsibility is an important feature of modern business. It involves a certain level of voluntary response to social problems, fulfillment of moral requirements set by society. Companies under martial law have already realized the advantages of a proactive social position and are increasingly and systematically involved in solving social, environmental and other problems of the state. But we have to think about how to rebuild Ukraine after the war and what needs to be done already during the war. This is important to ensure the country’s long-term survival, and it provides hope and direction for efforts today. Today, the combined efforts of business and the state make it possible to maintain the country’s economy. The experience of advanced companies has shown that the implementation of corporate social responsibility increases the investment attractiveness of companies of any industry. In recent years, the trend towards responsibility and environmental friendliness has spread to the sphere of investments and corporate management in all types of business activities. The application of ESG indicators - criteria and their evaluations reveal the activity of the company’s position, which consists in constant interaction with society in solving social problems. The profitability of the business took a back seat, because the organization of social orientation, the purpose of which is to help large, small and medium-sized businesses, non-governmental organizations, governments to quantitatively and qualitatively assess their economic, social and environmental impacts, in particular at the level of creating any product ( work, goods, services).Recently, especially urgent problems that arise when making decisions regarding the implementation of state construction projects based on the analysis of information about the activity of a business entity are very important and affect the management of competitiveness. The process of recovery of the Ukrainian economy is a constant source of financing for various investment projects. Practice shows that the costs of implementing management at the state level are continuously increasing, and the consequences of unsuccessful decisions are becoming more and more tangible. Modern market relations, challenges that arise in the economy and affect the economic activity of enterprises, determine the need to solve problems related to improving the quality of management of the enterprise’s competitiveness. The complexity and instability of the environment require the enterprise not to improve the forms and methods of management, but to radically change the principles of creating management and production systems. The author considered approaches to the application of management transformation according to ESG - criteria for enterprises in the construction industry, which create a new economic reality that requires management of constant changes, adaptation to the conditions of continuous crises, military threats, and financial instability. Making creative socially responsible decisions by management in the interests of current and future generations based on the best global practices of innovative, financial, environmental and social management will help restore the industrial potential of Ukraine.